2005
DOI: 10.1063/1.1883327
|View full text |Cite
|
Sign up to set email alerts
|

Ultrapure C60 field-effect transistors and the effects of oxygen exposure

Abstract: We report on electrical measurements of C60-based field-effect transistors (FETs) that were fabricated and characterized in an ultrahigh vacuum, and on how their properties are affected by progressive exposure to impurity gases. The in situ experiments demonstrated that oxygen-free devices have unipolar n-type characteristics with an electron field-effect mobility of up to 0.08cm2∕Vs immediately after fabrication, and up to 0.5cm2∕Vs after an annealing treatment in a high vacuum. Upon oxygen exposure, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 24 publications
(24 reference statements)
3
49
0
Order By: Relevance
“…Thus, if these impurities are subsequently removed from the semiconductor material, the device performance can be recovered. Similar results have been reported for FETs fabricated with C 60 as the organic semiconductor; [20] I ds was demonstrated to recover when the oxygen was removed by thermal annealing in high vacuum. Therefore, the performance recovery after TiO x deposition indicates the active scavenging role of the TiO x layer.…”
supporting
confidence: 85%
“…Thus, if these impurities are subsequently removed from the semiconductor material, the device performance can be recovered. Similar results have been reported for FETs fabricated with C 60 as the organic semiconductor; [20] I ds was demonstrated to recover when the oxygen was removed by thermal annealing in high vacuum. Therefore, the performance recovery after TiO x deposition indicates the active scavenging role of the TiO x layer.…”
supporting
confidence: 85%
“…Other reports using XPS to study degradation included focusing on the fullerene derivative [8,9]. The studies showed that oxygen uptake increased during exposure and suggested that the PC61BM undergoes both temporary and permanent chemical reactions with oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that C 60 is very sensitive to oxygen and water, which would induce the decrease of carrier mobility and the traps for electrons in C 60 layer. 35,36 In the conventional OSCs, the C 60 is adjacent to the top metal cathode, suggesting that it is vulnerable to the air atmosphere. Thus, the quick increase of R S can be ascribed to the carrier mobility decrease of C 60 layer with increasing exposing time.…”
Section: Introduction Introduction Introductionmentioning
confidence: 99%